Audio-Visual Media in Online Learning Pencak Silat Ementary School Students - Sutopo, Wisnu Guntur; Munir, Ali (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Modification-based learning is one strategy in an effort to increase interest in learning in students. One of them uses audio visual in learning pencak silat. This research aims to describe the process of improving Pencak Silat learning through audio-visual media in elementary school students. This research is class action research. The subjects in this study were grade IV elementary school students with a total of 31 students. The instrument used is a long jump performance test. The data analysis techniques used in this study are qualitative and quantitative descriptive. Based on the results of the study, it can be concluded that the improvement of step pattern results through audiovisual media in grade IV elementary school students are characterized by an increase in the average grade of students. The average score of students in pre-action activities was 71.60 with a completion percentage of 28.57%. This condition increased the average student's grades in cycle I, which was 74.8, and the percentage of completeness by 61.90%. However, the increase still did not reach the target set earlier. Then after continuing to cycle II, the average grade of the student pattern again increased by 78.47 with a percentage of completion of 95.23%. This shows that the target that has been set before has been achieved so that the research is stopped in cycle II. The process of learning step patterns using an audio-visual approach is dynamic and fun. The ability of student step patterns increased by being marked by all complete learners KKM (Minimum Completion Criteria) which is 75. Keywords: audio-visual, Pencak silat, step patterns, Student